United States of America. Significant achievements 2012 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in the United States during 2012 are identified, with respect to the needs and interests of the country, strengthening issues such as financing, sustainability, food security, risk management, food safety, technical cooperation, training, resilience against climate change and in insurance.